RESISTENSI BERBASIS ADAT: PERLAWANAN MASYARAKAT PULAU REMPANG, KOTA BATAM, KEPULAUAN RIAU, TERHADAP RENCANA PEMBANGUNAN REMPANG ECO CITY - Nor Fitri Ayuningmas; Andri Alfian; Novia Asiska Ramadani (Sekolah Tinggi Pariwisata Mataram, 2023)
Abundant natural resources and strategic geographical location show the superiority of a region's conditions. Not optimal utilization by the community is a factor for the government to plan development according to the target and needs of the region. The development of Rempang Eco City in Rempang area of Batam City by the Batam government is one form of strategic utilization as a step to improve the economic condition of Rempang area. Rempang Eco City is a new economic area project in Rempang Island, Batam, Riau Islands. The purpose of this research is to reveal the reasons and factors and motives that cause people to reject the mining plan in Rempang Village, Batam City, Riau Islands. This research uses qualitative method with secondary data source through literature study. The results of this study show that the efforts made by the government certainly require the consent of the local community through good communication, avoiding problems that might occur. However, if communication cannot go well, through the laws and rules of a country, development is still carried out. This is the trigger for a community social movement that is resistance to policies and actions that occur